Validating women's reports of antenatal and postnatal care received in Bangladesh, Cambodia and Kenya. Issue 4 (19th April 2020) - McCarthy, Katharine J; Blanc, Ann K; Warren, Charlotte; Bajracharya, Ashish; Bellows, Benjamin
Abstract : Background: Global indicators for monitoring progress in maternal and newborn health have tended to rely on contact coverage indicators rather than the content of services received. As part of the effort to improve measurement of progress in maternal and newborn health, this study examines how accurately women can report on information and health interventions received during an antenatal or postnatal health consultation at health facilities in Bangladesh, Cambodia and Kenya. Methods: We conducted secondary analysis of matched observation and client interview data to compare women's reports of care received at exit interview with observation by a trained third-party observer. We assessed indicator accuracy by calculating sensitivity, specificity, area under the receiver operating characteristic curve (AUC) and inflation factor (IF). Indicators considered to have both high individual accuracy (an AUC value of 0.70 or greater) and low population-level bias (0.75<IF<1.25) were considered to have acceptable validity. In addition, we considered the number of countries where both validation criteria were met. Results: For indicators of antenatal care, we found 16 of 18 indicators in Bangladesh, 3 of 6 in Cambodia and 3 of 8 in Kenya met both validation criteria. For postnatal care, we found evidence of acceptable validity for 6 of 8 indicators in Bangladesh, 5 of 14 in Cambodia and 3 of 16 in Kenya. In general, we documented higher validity for indicators related to concrete, observable actions, as opposed to information or advice given. Women were more likely to recall care received for themselves, rather than for their newborn. Conclusions: Women reported accurately on multiple aspects of antenatal and postnatal care. While we describe broad patterns in the types of indicators likely to be recalled with accuracy, differences by setting warrant further investigation. Findings inform efforts to better monitor the coverage and quality of maternal and newborn health interventions.